Broiler preference for light color and feed form, and the effect of light on growth and performance of broiler chicks. - Rierson, Rusty Del (Kansas State University, 2011)
Over the decades much has been discovered about the appropriate lighting management strategies for raising commercial meat-type poultry. Our knowledge of light preference, wavelength, intensity, intermittent lighting, and avian spectral sensitivity continues to improve our management strategies. In this work, a total of 5 experiments were conducted. The first 2 experiments investigated the effects of Light emitting diodes (LED) lights on growth performance of broiler chicks. Broiler chicks were raised under LED lights at different intensities: 5, 10, 15, 20, and 25 lux. A significant linear relationship (P < 0.05) was found in experiment 1 between body weight gain and light intensity. In experiment 2, a linear trend was noticed between body weight gain and light intensity. As the light intensity increased, chick weight increased. Feed: gain ratios were not affected by light intensity. The third experiment also examined growth performance using LED lighting as well as the effects of feed form and different lighting intensities upon behavior. The broilers fed a pelleted diet had significantly better performance than those fed crumbles. Under more intense light it was discovered that broilers spend significantly more time (P< .05) consuming feed compared to dim light. The fourth experiment focused on broiler preference for light color, and feed form during feeding. The broilers were offered either pelleted or crumbled feed and served under 4 different light colors: red, white, blue, and green. It was found that broilers statistically preferred pelleted feed, and white lighting, with red being the 2nd color choice of preference while green and blue were statistically not chosen. The fifth experiment focused on chick preference for feed color, when under different light color. One day old chicks were offered dyed feed: red, yellow, blue, green or light brown iv (control) under 5 different colors of light: red, yellow, blue, green, and white. It was found that chicks significantly preferred red dyed feed, especially under blue light. In conclusion, it was found that LED lights can have positive effects on broiler performance. Broilers show a preference for white lighting and pelleted feed. Young chicks show a preference for red dyed feed.
Keywords: Broiler; Behavior; LED; Light; Broiler preference; Animal Sciences (0475)